Cirrhosinones A-H, 24-hydroxy cevanine-type alkaloids from Fritillariacirrhosa. (May 2022) - Dong, Huiwen; Zhang, Yunhu; Wai Ming, Tse; Wang, Shuhui; Li, Jiawei; Fu, Shaobing; Zhang, Qingying; Zeng, Kewu; Tu, Pengfei; Liang, Hong
Abstract: Eight undescribed isosteroidal alkaloids cirrhosinones A-H (1 –8 ), along with six known isosteroidal alkaloids (9 –14 ), were isolated from the bulbs of Fritillaria cirrhosa D. Don. Their structures were determined by HRESIMS and 2D NMR analysis, and their absolute configurations were established by X-ray analysis. Compounds 1 –8 possessed a typical cevanine-type alkaloid skeleton with a hydroxyl group rarely substituted at C-24 and compounds 4 –8 possessed rare 7 α or 7 β -hydroxyl groups. This was the first report of both C-7 and C-24 hydroxyl groups substituted cevanine-type alkaloids. In addition, an approach for distinguishing D/E cis and trans conformations of cevanine-type alkaloids by 1 H NMR data was developed. Moreover, the correlations between the relative configurations of 3-OH, 7-OH, 22-C, 24-OH, and 25-Me and the 1 H NMR and 13 C NMR data were also summarized. Compounds 1 –9 exhibited moderate NO inhibitory activities in LPS-stimulated BV-2 cells at the concentration of 40 μM. The acetylcholinesterase inhibitory activities of compounds 1 –7 and 9 –10 were also evaluated and none of them showed acetylcholinesterase inhibitory activities at the concentrations of 20–80 μM. Graphical abstract: 14 isosteroidal alkaloids including 8 unreported ones were isolated from the bulbs of Fritillaria cirrhosa D. Don. and their NO inhibitory and AChE inhibitory activities were evaluated. Image 1 Highlights: Eight undescribed 24-hydroxy cevanine-type alkaloids were isolated from Fritillaria cirrhosa. The absolute configurations were elucidated by 2D NMR analysis and X-ray analysis. The D/E cis and trans conformations of cevanine-type alkaloids were distinguished by 1 H NMR data. Determination of the relative configurations of cevanine alkaloids by NMR data was summarized. NO inhibitory and AChE inhibitory activities of the isolates were evaluated.